Adenosine 5′ phosphosulfate reductase and sulfite oxidase regulate sulfite-induced water loss in Arabidopsis. (9th June 2021) - Bekturova, Aizat; Oshanova, Dinara; Tiwari, Poonam; Nurbekova, Zhadyrassyn; Kurmanbayeva, Assylay; Soltabayeva, Aigerim; Yarmolinsky, Dmitry; Srivastava, Sudhakar; Turecková, Veronika; Strnad, Miroslav; Sagi, Moshe
Abstract : Sulfite, maintained by the activities of APS reductase and sulfite oxidase, induce water loss through increase in stomatal apertures, acting opposite to sulfate and ABA signaling. Abstract: Chloroplast-localized adenosine-5'-phosphosulphate reductase (APR) generates sulfite and plays a pivotal role in reduction of sulfate to cysteine. The peroxisome-localized sulfite oxidase (SO) oxidizes excess sulfite to sulfate. Arabidopsis wild type, SO RNA-interference ( SO Ri) and SO overexpression ( SO OE) transgenic lines infiltrated with sulfite showed increased water loss in SO Ri plants, and smaller stomatal apertures in SO OE plants compared with wild-type plants. Sulfite application also limited sulfate and abscisic acid-induced stomatal closure in wild type and SO Ri. The increases in APR activity in response to sulfite infiltration into wild type and SO Ri leaves resulted in an increase in endogenous sulfite, indicating that APR has an important role in sulfite-induced increases in stomatal aperture. Sulfite-induced H2 O2 generation by NADPH oxidase led to enhanced APR expression and sulfite production. Suppression of APR by inhibiting NADPH oxidase and glutathione reductase2 (GR2), or mutation in APR2 or GR2, resulted in a decrease in sulfite production and stomatal apertures. The importance of APR and SO and the significance of sulfite concentrations in water loss were further demonstrated during rapid, harsh drought stress in root-detached wild-type, gr2 and SO transgenic plants. Our results demonstrate the role of SO in sulfite homeostasis in relation to water consumption in well-watered plants.